(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Numerous methods have been proposed to interpolate and extrapolate of missing temporal data series such as rainfall, temperature, humidity, runoff storms…etc. Whereas there are many of other method for estimating spatial missing data such as groundwater levels and topography. On the other hand,many methods were developed to evaluate their efficiencies,but the uncertainty of results is rarely calculated. In this study, three interpolation methods have been compared to estimate missing spatial topographical data in the ancient Babylon City. The model domain was discretized into a number of horizontal (19) cells and vertical (23) cells. Five observed elevation remarks were used to estimate the unknown elevations of 257 remarks. The new method namely Nearest Tri-Point Interpolation (NTPI) was compared with the Inverse Distance Weighting (IDW) and surfer techniques. The efficiency of these techniques was calculated by the Average Error (AE) and Standard of Deviation (SD). The (NTPI) technique offers results of less AE and SD as well as more accuracy in ground surface elevations distribution